2011
DOI: 10.1128/jvi.05038-11
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Mammalian Species-Infectious and -Pathogenic Avian Influenza H6N5 Virus with No Evidence of Adaptation

Abstract: The migratory waterfowl of the world are considered to be the natural reservoir of influenza A viruses. Of the 16 hemagglutinin subtypes of avian influenza viruses, the H6 subtype is commonly perpetuated in its natural hosts and is of concern due to its potential to be a precursor of highly pathogenic influenza viruses by reassortment. During routine influenza surveillance, we isolated an unconventional H6N5 subtype of avian influenza virus. Experimental infection of mice revealed that this isolate replicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 31 publications
3
28
0
Order By: Relevance
“…The A/aquatic bird/Korea/ CN5/2009 (H6N5) [A/AB/Kor/CN5/09 (H6N5)] strain was isolated from fecal swabs of aquatic birds in 2009. Surprisingly, it showed infectivity and pathogenicity in mammalian species without evidence of adaptation (6). To date, primers targeting the noncoding regions (NCRs) have generally been used to obtain complete genomes of influenza A viruses.…”
mentioning
confidence: 99%
“…The A/aquatic bird/Korea/ CN5/2009 (H6N5) [A/AB/Kor/CN5/09 (H6N5)] strain was isolated from fecal swabs of aquatic birds in 2009. Surprisingly, it showed infectivity and pathogenicity in mammalian species without evidence of adaptation (6). To date, primers targeting the noncoding regions (NCRs) have generally been used to obtain complete genomes of influenza A viruses.…”
mentioning
confidence: 99%
“…Although the H6 viruses isolated to date have largely caused asymptomatic infections in waterfowl, infection of chickens with H6 viruses has been associated with decreased egg production, upper respiratory tract infection, morbidity, and increased mortality (10)(11)(12)(13). Several studies have shown that certain H6 viruses can infect and cause illness in mice and ferrets (26,27). An H6N6 virus was also detected in pigs in Guangdong province in China in 2010 (28), and an H6N1 virus was isolated from a human with flu-like symptoms in Taiwan in 2013 (29).…”
mentioning
confidence: 99%
“…The result of these evolutionary dynamics can manifest as decreased parasitism and virulence in the initial host species and increased virulence in new hosts (Ebert 1998). Introduction need not lead to increased pathogen specialization, though, since coevolution can also favour generalist strategies (Hall et al 2011) and host-switching does not always require adaptation by the pathogen (Nam et al 2011).…”
Section: Introductionmentioning
confidence: 99%